Effectiveness of Legal Protection on Heirs in Dispute on Sale and Purchase of Inherited Land - Muhammad Rizky Eka Pratama; Bambang Tri Bawono; Amin Purnawan; R. Sugiharto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this study is to find out and analyze: 1) The legal consequences of a dispute over the sale and purchase of inherited land without the consent of the heirs. 2) The effectiveness of legal protection for heirs in disputes over the sale and purchase of inheritance land against the law in Surabaya. The approach method used in this study is an empirical juridical approach. The specification of the research used is descriptive analytical research. This type of data uses primary and secondary data. The data analysis method used qualitative data analysis. The results of the study concluded: 1) The legal consequences of the dispute over the sale and purchase of inheritance land without the consent of the heirs are that the land is sold by people who are not entitled to sell it (because those who now hold ownership rights to the land are the heirs), therefore the sale and purchase cancelled. As a result of the law with the cancellation of the sale and purchase, the sale and purchase is considered to have never existed, and each party is returned to its original state before the